Programmable magnetoinductive devices - Stevens, C; Shamonina, E; Paszkiewicz, J (Institute of Electrical and Electronics Engineers, 2016)
A design for a programmable magnetoinductive waveguide where the impedance of each cell can be set to one of two values by an electronic signal is presented. A 1D magnetoinductive waveguide using such cells is verified experimentally and used to demonstrate an electronically programmable transfer function. Extension of the concept to 2D devices and creating programmable RF systems is discussed.